Case Report: Pediatric immune-mediated necrotizing myopathies mimicking inherited muscle disorders: clinical, paraclinical, and genetic insights from two cases - Gianmarco Severa; Maria Camila Cortes-Rojas; Marta Gomez-Garcia de la Banda; Thibaut Belmondo; Audrey Benezit; France Leturcq; Camille Verebi; Baptiste Periou; Eduard Gallardo; Denise Cassandrini; Thierry Gendre; Sophie Hue; et al. (Frontiers in Pediatrics, 2026)
Objectives Immune-mediated necrotizing myopathies (IMNMs) are a group of rare acquired myopathies. We describe two pediatric cases presenting with early-onset proximal and axial muscle weakness, rhabdomyolysis, and progressive evolution mimicking limb-girdle muscular dystrophy. Methods This retrospective case series is based on a review of the medical records of two pediatric IMNM patients with symptom onset at 2 (P1) and 16 (P2) years of age and diagnoses at 5 and 17 years, respectively. Both patients underwent clinical assessment, muscle biopsy, whole-body muscle MRI, a testing for myositis-specific and myositis-associated autoantibodies, whole-exome sequencing, and in silico analysis following informed parental consent. These data were collected and analyzed retrospectively. The manuscript was prepared in accordance with the CARE reporting guidelines. Results Both patients presented with an early onset of severe muscle weakness, compatible with the clinical suspicion of limb-girdle muscular dystrophy. P1’s serological screening was positive for anti-signal recognition particle antibodies, and muscle biopsy revealed a myopathological pattern compatible with IMNM. Treatment with corticosteroids, intravenous immunoglobulin (IVIG), and rituximab resulted in partial amelioration of muscle strength. P2’s screening for myositis autoantibodies was negative. Muscle biopsy showed a dystrophic pattern with the absence of dysferlin. Whole-exome sequencing did not identify any compatible variants explaining the muscle phenotype in both patients. P2 was treated with corticosteroids, IVIG, and rituximab, resulting in normalization of muscle weakness and creatine kinase (CK) levels. Conclusion IMNM should be considered in pediatric patients with clinical and paraclinical suspicion of inherited muscular dystrophy. Serological testing is crucial for identifying seropositive cases. In the presence of seronegative or more complex cases, a global paraclinical and genetic analysis is essential to avoid misdiagnosis and initiate long-term immunosuppressive therapy, including corticosteroids, IVIG, and rituximab.